FAKTOR-FAKTOR YANG MEMPENGARUHI PENGELOLAAN ALOKASI ANGGARAN PROGRAM DESA MAJU INHIL JAYA (DMIJ) DI DESA KEMBANG MEKAR SARI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2014 - Oky Aditya Pranata; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
DMIJ Program is a program of the Government of Indragiri Hilir which is funded from the budget Indragiri Hilir. Through the Program Desa Maju Jaya Inhil Kembang Mekar Sari village self-help group with a population of 2681 inhabitants comprising several ethnic groups include Malays, Bugis, Banjar, Java and tiong hua. This research problem formulation What factors affect the Budget Allocation Management Program (DMIJ) in Kembang Mekar Sari subdistrict Keritang Inhil District. The purpose of this study to determine Management Budget Allocation Program Desa Maju Inhil Jaya (DMIJ) in Kembang Mekar Sari subdistrict Keritang Indragiri Hilir 2014 and to determine the factors that affect the Management Budget Allocation Program Desa Maju Inhil Jaya (DMIJ) Village Kembang Mekar Sari subdistrict Keritang Indragiri Hilir 2014. this research was conducted in Kembang Mekar Sari subdistrict Keritang. The method used is a qualitative research, data collection techniques are interviews, observation and documentation. Based on the findings that the process of planning, budgeting, disbursement mechanisms have been run in accordance with the PTO DMIJ. While in the process of using Budget Allocation Program DMIJ already well underway, although still not optimal. The functional supervision of supervision conducted by the District Government and the District Government Inhil Keritang the form of reporting, should be done every month (Periodic Report). However, in practice only done twice. The fact has not happened yet direct supervision by the community in the management of Program Budget Allocation DMIJ. Actual administrative accountability has not been carried out correctly, which is held only twice, in the reporting process phase I and phase II. Public participation was one of the factors that support the management of Program Budget Allocation DMIJ. Culture of mutual aid society is the potential of the village in the management of Program Budget Allocation DMIJ in community empowerment. Low Human Resources by the village and the villagers is the main bottleneck management DMIJ Program Allocation Budget. Keywords : Factors Affecting Program DMIJ